DIGITAL LEARNING EDUCATION DEVELOPMENT TOWARDS MODERN ISLAMIC CULTURE: A STRENGTHENING “MERDEKA BELAJAR” STRATEGY - Enung Nugraha; Muhamad Fauzi (Al Qalam, 2020)
Technological progress has a significant force in competition in all areas of life. Indonesian human resources achieve a demographic bonus with millennials who are adapting to today's popular digital culture. Increasingly providing real value to every millennial activity, especially in education, will provide more innovative additions. Islamic teachings teach every Muslim to adapt to cultural and educational developments to compete in all fields. Everyday using digital learning and the rigid understanding of Islamic culture's modernization causes Islamic education's quality and competition to be less than optimal. The Covid-19 pandemic creates a learning adaptation gap that prioritizes social distancing guards so that the government needs to formulate policies with 'Merdeka Belajar' that aim to achieve learning effectiveness. This research aims to examine digital learning's role in Muslim culture and school readiness for digital education development. This research uses quantitative methods with a descriptive analysis approach with secondary data as the data source. The research results in informal education have become the focus of effective learning supported by modern Islamic culture, where Islamic schools in Indonesia can adapt to current technological advances. Schools and educational institutions are ready with infrastructure in school learning using computers and internet networks and educational technology companies to implement digital education. The implication of 'Merdeka Belajar' of government policy is strengthening strategy through collaboration adaptive of digital learning education and modern Islamic culture with schools readiness and industries supporting to realize a learning system through digital technology.